2007
DOI: 10.1111/j.1440-1681.2007.04751.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Performance and Ventilatory Efficiency in Patients With Mild and Moderate Liver Cirrhosis

Abstract: 1. The impact of ventilatory efficiency on reduced exercise capacity and recovery oxygen kinetics has not been addressed in cirrhotic patients. The aim of the present study was to investigate exercise performance and ventilatory efficiency in patients with mild and moderate liver cirrhosis (LC). 2. Nineteen male non-hypoxic patients with LC (age 51.3 +/- 9.1 years; body mass index (BMI) 25.6 +/- 3.6 kg/m(2)) classified by the Child-Pugh score as class A (n = 7) and class B (n = 12) and 19 age- and BMI-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
22
1
1
Order By: Relevance
“…Patients with hepatic cirrhosis have previously presented lower values of maximal oxygen consumption when compared to subjects not affected with the disease (21,23,24,26,32). One of these studies (23) did not find any significant difference on VO 2max when patients were compared to healthy subjects.…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…Patients with hepatic cirrhosis have previously presented lower values of maximal oxygen consumption when compared to subjects not affected with the disease (21,23,24,26,32). One of these studies (23) did not find any significant difference on VO 2max when patients were compared to healthy subjects.…”
Section: Methodsmentioning
confidence: 91%
“…Even though some studies did not find a negative correlation between exercise capacity and Child-Pugh scoring (21,22,34,35), it has been suggested that hepatic cirrhosis can affect cardiorespiratory capacity during exercise (24,25,27,28,30,32).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations